The colic miserere as a diagnosis of appendicitis in the times of the Viceroy Marquis of Guadalcázar according to the story «Los panecitos de San Nicolás» - Aguilar Espino, Linda Estefani (2022)
In this article we will analyse the tradition «Los panecitos de San Nicolás» by Ricardo Palma. We hypothesize that miserere colic is a symptom of appendicitis. Furthermore, we are interested in studying how this disease was cured in the times of the Peruvian viceroyalty based on the use of culén and hierbaluisa as an alternative treatment, whose benefits were to reduce inflammation to treat strong colic, eliminate the discomfort caused by excessive food consumption, among others.